2016
DOI: 10.1088/1748-0221/11/10/t10001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability test of a triple GEM detector

Abstract: The main aim of the study is to perform the long-term stability test of gain of the single mask triple GEM detector. A simple method is used for this longterm stability test using a radioactive X-ray source with high activity. The test is continued till accumulation of charge per unit area > 12.0 mC/mm 2 . The details of the chamber fabrication, the test set-up, the method of measurement and the test results are presented in this paper.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…So the intrinsic gain variation will not affect the result.) In this study, we have arrived at a conclusion that no ageing is observed till the accumulation of charge per unit area > 12.0 mC/mm 2 [56]. However, in this experiment, we have only monitored the gain of the detector and investigated its stability under continuous radiation.…”
Section: Experiments Details and Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…So the intrinsic gain variation will not affect the result.) In this study, we have arrived at a conclusion that no ageing is observed till the accumulation of charge per unit area > 12.0 mC/mm 2 [56]. However, in this experiment, we have only monitored the gain of the detector and investigated its stability under continuous radiation.…”
Section: Experiments Details and Resultsmentioning
confidence: 94%
“…The count rate is found to increase with the increase of HV and reaches a plateau. At plateau, the count rate is found to be ∼ 350 kHz [56].…”
Section: Gas Chambermentioning
confidence: 99%
See 3 more Smart Citations